2018
DOI: 10.1021/acs.cgd.8b01335
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Three Two-Fold Interpenetrated Metal–Organic Frameworks: Luminescent Zn/Cd-Metal–Organic Frameworks for Detection of 2,4,6-Trinitrophenol and Nitrofurazone in the Aqueous Phase

Abstract: Through a dual-ligand strategy, three mixed ligands metal–organic frameworks (MOFs), namely, {[Zn2(Py2TTz)2­(BDC)2]­·2­(DMF)­·0.5­(H2O)} n (1), {[Cd2(Py2TTz)2­(BDC)2]­·2­(DMF)} n (2), and {[Co2(Py2TTz)2­(BDC)2]­·2­(DMF)­·0.5­(H2O)} n (3) (where Py2TTz = 2,5-bis­(4-pyridyl)­thiazolo­[5,4-d]­thiazole, BDC = 1,4-benzenedicarboxylate, and DMF = N,N-dimethylformamide), were synthesized under solvothermal conditions. The single-crystal X-ray diffraction analyses reveal that the three MOFs possess similar 2-fold i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(67 citation statements)
references
References 80 publications
2
65
0
Order By: Relevance
“…However, the luminescence intensities of compounds 5 – 7 are slightly weaker than those of the corresponding ligands 1,4‐H 2 NDC and 2,6‐H 2 NDC. It which may be attributed to the ligand to metal coordination effects, which reduces rigidity of the ligand and increases the nonradiative energy loss . The complicated luminescence properties of compounds 1 – 9 may originate from the differences in the auxiliary dicarboxylate ligands and various coordination environments around d 10 metal ions, as well as the conformations and coordination modes of the ligands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the luminescence intensities of compounds 5 – 7 are slightly weaker than those of the corresponding ligands 1,4‐H 2 NDC and 2,6‐H 2 NDC. It which may be attributed to the ligand to metal coordination effects, which reduces rigidity of the ligand and increases the nonradiative energy loss . The complicated luminescence properties of compounds 1 – 9 may originate from the differences in the auxiliary dicarboxylate ligands and various coordination environments around d 10 metal ions, as well as the conformations and coordination modes of the ligands.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that some MOFs were constructed from rigid dicarboxylate and functionalized bipyridine by the mixed‐ligand strategy, which have intriguing structures and excellent properties . 2,5‐Bis(4‐pyridyl)thiazolo[5,4‐ d ]thiazole (Py 2 TTz) with rigid π‐conjugated system has good luminescence property , . Meanwhile, it integrates the features of both thiazolo[5,4‐ d ]thiazole and pyridine, possessing multiple coordination sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPs have a diversity of structures since multiple coordination environments of transition metal ions. For example, Zn, Cu, Cd, Ni, and Co can adopt four‐, five‐, or six‐coordinate geometries, leading to the extended CPs from 1D to 3D dimensionality However, CPs based on the transition metal ions without unpaired electrons, especially those with d 10 configurations of Zn/Cd, can yield linker‐based high emission . So, the Zn/Cd‐luminescence coordination polymers were studied for luminescence sensing of the analytes .…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence quenching might also be related to the stronger electron‐withdrawing ability of TNP . Here the introduced TNP changes the excited‐state electron transferring path of photoluminescence material, preventing the electronic return to the ground‐state energy levels . The organic aromatic ligand acts as the electron donor due to its electron‐rich nature.…”
Section: Introductionmentioning
confidence: 99%